Design of Straight Motion Subjects Based on Avs Video Editor Software - Ahmad, Ahmad; Anshori, Achmad (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2016)
The aim of this research is to obtain a media result from the process of designing physics learning media for class X based on AVS Video Editor Software, and to find out the responses of class X teachers and students regarding the results of designing physics learning media using AVS Video Editor Software. This learning media is first validated by a team of experts, in this case lecturers, where the expert team consists of a team of media experts and a team of material experts. The design product was tested on small groups of students, namely 20 students. The perception level is calculated using a percentage formula. The results of the analysis of student responses to the designed physics teaching materials show that the educational dimension percentage value of 92 is classified as very good. The display dimensions of teaching materials are 92.5%, so they are in the very good category. Likewise, the percentage value for teaching material scenarios is 94.83%, which is classified as very good. Based on the results of this research, it can be concluded that the designed teaching materials can be declared as appropriate media for use in the learning process.